Modification of cell surfaces by enzymatic introduction of special sialic acid analogues - Kosa, Renate E.; Brossmer, Reinhard; Groß, Hans Jürgen (Biochemical and biophysical research communications, 1993)
Taking advantage of the defined acceptor specifity of rat liver α2,6-sialyltransferase, N-linked Ga1β1,4GlcNAc-sequences of glycoconjugates at the plasma membrane of viable human erythrorytes and lymphoblastic IN-9 cells were modified to terminate in three NeuAc analogues endowed with special bemchemical properties: sialidase-resistant 9-amino-NeuAc, O-acetylesterase-resistant 9-acetamido-NeuAc and photolabile 9-azido-NeuAc. Incorporation of the latter analogues and of parent NeuAc proceeded to similar values, whereas 9-amino-NeuAc yielded slightly reduced values.